Adaptive Educational Hypermedia Systems in Technology Enhanced Learning: A Literature Review - ARNEDILLO, INMACULADA; MULWA, CATHERINE (ACM, 2010)
This literature review focuses on the educational benefits afforded to learners by Technology Enhanced Learning Environments (TELE) which adapt and personalize the learning experience. More specifically it focuses on Adaptive Educational Hypermedia Systems (AEHS) that incorporate Learning Styles. Adaptive approaches to learning offer alternatives to the traditional ?One- size-fits-all? approach and have driven the development of dynamic educational environments. The use of such environments can deliver educational benefits as educational offerings are personalised based upon various characteristics of individual learners.
ACM Special Interest Group for Information Technology Education Conference, SIGITE
PUBLISHED
Central Michigan University, Midland, MI, USA
Keywords: Computers and Education; Technology Enhanced Learning; Intelligent Content & Communications; Smart & Sustainable Planet